El espectáculo teatral como objeto artístico: el manuscrito de la Fábula de Andrómeda y Perseo - Francisco Sáez Raposo. (Mélanges de la Casa de Velázquez)
This paper studies the totalizing purpose with which the manuscript of the Fable of Andromeda and Perseus, a mythological drama written by Pedro Calderón de la Barca, was conceived. With a very innovative approach, its goal goes beyond preserving a literary text, as it seeks to transmit an entire show as a whole, that is, the possibility of reliving, for someone who was not present, an experience in an intense way. To do this, various elements are interwoven (the literary text, a series of drawings, the score of the feast and a report of the performance) that, decoded in a symbiotic and convenient way by a trained reader, can generate images and sensations from the use of aesthetic memory. A key piece in this process is the anonymous description that details the development of the performance, absolutely neglected by critics until now.